Conservative management of asymptomatic vertebral artery stent fracture with fragment embolisation to V3 segment: a case report - Hou, Bin; Li, Chuangzhong; Cao, Yuan; Wang, Xiaogang; Gao, Dandan; Chen, Ligang (Frontiers in Surgery, 2025)
IntroductionStent fracture represents a recognised but rare complication tied to vertebral artery origin stenting.MethodsWe present a male who was diagnosed with left vertebral artery origin stenosis due to vertigo and diplopia, and who was deployed with a rapamycin-eluting stent. One-year follow-up computed tomography angiography demonstrated mid-stent fracture with distal fragment migration into the V3 segment, but the patient was asymptomatic and managed medically with close surveillance.ResultsThis case elucidates that rapamycin-eluting stents are an effective treatment for stenosis at the vertebral artery origin.DiscussionsIn rare instances involving complete stent fracture and migration of distal debris, conservative management may be a feasible option for asymptomatic patients.